DOI: 10.31274/rtd-180813-15237
|View full text |Cite
|
Sign up to set email alerts
|

Breeding behavior at successive generations following hybridization in soybeans

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. UMI UMI Microform DP13314

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
3
29
1
Order By: Relevance
“…The low yielding crosses could therefore be rejected without fear that a large number of high yielding crosses were being discarded. This is in marked contrast to the results reported for soya beans (KALTON, 1948;WEISS et al, 1947), where even when all the generations were grown in the same year, there was no relationship between cross yields over generations. The authors attributed this failure to strong, but inconsistent selection pressure for maturity caused by the time of the first frost at the end of the growing season of the previous year.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The low yielding crosses could therefore be rejected without fear that a large number of high yielding crosses were being discarded. This is in marked contrast to the results reported for soya beans (KALTON, 1948;WEISS et al, 1947), where even when all the generations were grown in the same year, there was no relationship between cross yields over generations. The authors attributed this failure to strong, but inconsistent selection pressure for maturity caused by the time of the first frost at the end of the growing season of the previous year.…”
Section: Discussioncontrasting
confidence: 56%
“…Varieties or crosses that are genetically low yielding, but which have a measure of resistance to pests and diseases, as might occur in wild, weedy or primitive types, may perform better in stress situations than varieties or crosses of high yield potential but no resistance. This effect is similar to that of frost in determining yield and maturity in soya bean crosses (KALTON, 1948, WEISS et al, 1947. Therefore to select crosses or genotype of high yield potential, it is important to analyse and separate possible confounding factors which may cause yields to vary.…”
Section: Discussionmentioning
confidence: 97%
“…Bulk populations were of limited predictive value for lodging and height, while measurements of yield and maturity had little meaning as bulk population measurements. Similarly, Kalton (1948) reported that ?£ spaced plant and line yield tests were of little predictive value, while P2 spaced plant meas urements for plant height and maturity provided good estimates of progeny performance. Significant genotype x environment interactions were reported by Torrie (1958) for several plant characters in soybeans.…”
Section: Early Generation Testing and Gene Actionmentioning
confidence: 97%
“…Because of the gene interaction mentioned, the cultural value (phenotype) of a heterozygous plant is not a reliable guide to the value of the lines which may be derived from it . In fact plants that might segregate valuable gene combinations after selfing, could easily get lost, if plants, dominant or intermediate for some detrimental genes, are eliminated from highly heterozygous populations by means of phenotypic selections (1,4,9) . 3 …”
Section: Genetics and Yieldmentioning
confidence: 99%